UPAYA PEMERINTAH INDIA DALAM MENGENDALIKAN KONSUMSI TEMBAKAU MELALUI RATIFIKASI WHO FRAMEWORK CONVENTION ON TOBACCO CONTROL TAHUN 2004-2009 - Maheswari, I Gusti Ayu Chandra; Dewi, Putu Ratih Kumala; Priadarsini, Ni Wayan Rainy (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2017)
ABSTRACT The high rate of tobacco consumption that affect health and mortality in India, become a main problems faced by the government. Consuming smoke and chewing tobacco widespread among adults, women to children. The Indian government seeks to control tobacco consumption problems by ratifying international agreements called Framework Convention on Tobacco Control (FCTC), which was initiated by the World Health Organization (WHO) in 2004. The Government of India take steps to implement the provisions of the FCTC by developing National Tobacco Control Program (NTCP) as public policy on tobacco control. This study aims to describe how the Indian government's efforts to control tobacco consumption by ratifying FCTC. This study assessed using the concept of international agreements and public policy. Keywords: Tobacco consumption,